An Approach for Pre-Diagnosis Information Literacy Level by Using Expert System - Maria Ulfah S; Joko Munandar (IJID (International Journal on Informatics for Development), 2012)
Communication and information technology has been equipped almost human lives sector. Inevitably, in spite of its positive impacts, this advance opens to vulnerable things, even dangerous to human generation. Pornography, violence and immoral activities, get advantages from global net between people Therefore, it is necessary for anybody to possess filter about what is, from where, when and how much information that he/she needs, which is information literacy. Students are not different with that fact. It is not only for filtering information, but this capability is also for creating a human learner who is self-directed, active learner, dynamic, and innovative. Whereas, indeed, these aspects are crucial in student centered learning which is commonly adapted in university.This paper gives an introduction for pre-diagnosis level of information literacy by designing and implementing rule-based expert system. This system mimics expertise of one expert by formulating knowledge as rules. Knowledge which is intended in this proposed system is information literacy for higher education in science and technology/engineering field.